Binominal constructions in Italian of the N1-di-N2 type: towards a typology of Light Noun Constructions. (January 2016) - Masini, Francesca
Abstract: Whereas a number of works have investigated N1- of- N2 binominal constructions in English (especially of the sort / kind of type), much less attention has been paid to the corresponding constructions in Romance languages, especially Italian. This paper will provide an overview of Italian binominal constructions with the preposition di 'of' (N1- di- N2), which are associated with a variety of functions, such as approximation, aspect, evaluation, modification, possession, quantification, subcategorization. Not all constructions, however, behave alike: some of them are special in that the first noun is not fully referential and does not function as a prototypical phrasal head, but rather as a "Light Noun" that carries a grammatical meaning that is applied to the second noun. The various constructions thus identified – named "Light Noun Constructions" – are shown to be part of constructional networks, which go from micro-constructions to macro-constructions, and possibly "meta-constructions", a maximally general constructional level that licenses all Light Noun patterns.